Medication Errors During Medication-Use Process - Nazari, Qand Agha (Journal of Natural Sciences – Kabul University, 2022)
Medication errors are a global concern, particularly in Afghanistan, where they impose significant clinical and economic burdens. This study aimed to review medication errors during the medication-use process. The prevalence of such errors varies across different stages, including prescribing, transcribing, dispensing, administration, and monitoring. These errors can occur at any step of the process, involving physicians, pharmacists, and nurses. Medication errors manifest in various forms and can lead to harmful consequences. Therefore, heightened attention to each stage of the medication-use process is essential to prevent errors and mitigate their adverse effects.